Phenomenology: Brain Rot in Gen Z Reviewed from the Perspective of the Cognitive Behavioral Therapy (Cbt) Approach - Rahmat Hidayat; Wangid, Muhammad Nur (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
This study aims to analyze the phenomenology : brain rot in Gen Z is reviewed from perspective cognitive behavioral therapy approach . This study uses a qualitative approach with method phenomenological , Study This held at SMAN 9 Pekanbaru , Participants in study This are 10 students from SMAN 9 Pekanbaru who were selected purposively . Technique primary data collection in study This is interview and observation in-depth semi- structured , Data Analysis Data analysis was performed use technique analysis developed phenomenological? by Colaizzi . The results of the study showed the phenomenon of brain rot in students of SMAN 9 Pekanbaru impact on decline function cognitive, disorders emotions, and difficulty regulation self consequence excessive digital media consumption. reflects impact significant to mental health and behavior Study students . Cognitive Behavioral Therapy (CBT) is assessed effective in help student recognize pattern think negative , increase control self, and reduce digital addiction . Research This recommend implementation of counseling program based on Cognitive Behavioral Therapy ( CBT ) in schools For support students ' mental health in the digital age. in map impact psychological brain rot and push development approach based on proof For support students' mental health in the digital age.